The Economic Impact on Households and Nations of NCDs : A Review of Existing Evidence - Engelgau, Michael; Rosenhouse, Sandra; El-Saharty, Sameh; Mahal, Ajay (Taylor and Francis, 2013)
In developing countries, the noncommunicable disease (NCD) and risk factor burdens are shifting toward the poor. Treating chronic diseases can be expensive. In developing countries where generally much health care costs are borne by patients themselves, for those who live in poverty or recently escaped severe poverty, when faced with large, lifelong out-of-pocket expenses, impoverishment persists or can reoccur. These patterns have implications for national economic growth and poverty-reduction efforts. NCDs can change spending patterns dramatically and result in significantly reducing non–medical-related spending on food and education. In India, about 40% of household expenditures for treating NCDs are financed by households with distress patterns (borrowing and sales of assets). NCD short- and long-term disability can lead to a decrease in working-age population participation in the labor force and reduce productivity and, in turn, reduce per capita gross domestic product growth. To fully capitalize on the demographic dividend (i.e., aging of the population resulting in less dependent children, not yet more dependent elderly, and greater national productivity), healthy aging is necessary, which, in turn, requires effectively tackling NCDs. Last, from an equity standpoint, the economic effect of NCDs, evident at the household level and at the country level, will disproportionately affect the poor and vulnerable populations in the developing world.